PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA PT. EKA PUTRA PRADA - Ardian, M. Rayhan; Fadli, Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine the influence of product quality, service quality and price on consumer satisfaction at PT. Eka Putra Prada. The method used in this research is descriptive statistical analysis and multiple linear regression. The sample in this study amounted to 94 respondents using the Slovin method and using questionnaires and interviews as research instruments. Through instrument tests and data analysis techniques which include validity tests, reliability tests, classical assumption tests, regression equation tests, partial tests, simultaneous tests, and coefficient of determination tests, the results were obtained that product quality assessment (X1) has a positive and significant effect on consumer satisfaction. (Y), service quality (X2) has a positive and significant effect on consumer satisfaction (Y), price (X3) has a negative effect on consumer satisfaction (Y) and assessment of product quality (X1), service quality (X2) and price (X3) significant effect on consumer satisfaction (Y) at PT. Eka Putra Prada. Keywords: Product Quality, Service Quality, Price and Consumer Satisfaction.